Strengthening local government capability the case of the provincial development assistance project - Iglesias, Gabriel U. (Philippine Journal of Public Administration, 1983)
The Provincial Development Assistance Project (PDAP) as a development strategy was examined to identify the problems and issues relative to strengthening the capability of local governments to plan and manage development programs and projects. Focusing on the PDAP experience in Pangasinan, the project's implementation was analyzed in terms of: (1) improving organizational and management processes; (2) developing a group of competent managerial and technical personnel; (3) increasing financial resources and improving the allocation process; and (4) increasing engineering/infrastructure capability. Factors were identified which influence the implementation of PDAP, namely: (1) the political leadership, (2) the technical/administrative leadership; and (3) the presence of a technically qualified full-time staff.